-(-x+18)=

Simple and best practice solution for -(-x+18)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-x+18)= equation:


Simplifying
-1(-1x + 18) = 0

Reorder the terms:
-1(18 + -1x) = 0
(18 * -1 + -1x * -1) = 0
(-18 + 1x) = 0

Solving
-18 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 1x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 1x = 0 + 18
1x = 0 + 18

Combine like terms: 0 + 18 = 18
1x = 18

Divide each side by '1'.
x = 18

Simplifying
x = 18

See similar equations:

| 8x+7=-3(5x-4) | | y*2+9y*2= | | m-15=3(m-4)-2m | | 617=25k-8 | | 9(p-8)=18 | | 3m+2m=8 | | x-1+15=x-1+9 | | -x+8y=-32 | | 5(x-3)+8=7x-10 | | 4-4x=-3x | | 18(k+12)=936 | | 2x+3x+3x+32=360 | | 14(x+30)=-196 | | v/9-5=(-6) | | z2=9/16 | | 19=-9(8c-3) | | 7v+1+6v= | | 2g+2g-4=43 | | 3-3(x-4)=-3-2 | | b/9=3 | | -3(x+7)=6x-39 | | -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 |

Equations solver categories